A influência da colaboração no desempenho da gestão da cadeia de suprimentos do café orgânico - Coti-zelati, Paolo Edoardo (2013)
Supply chain management (SCM) is a concept that began to be explored from the 1980s, became a subject of fundamental importance to the academic and business career. Successfully applied in various areas of business, the SCM is studied by researchers worldwide. This form of management discussion brings to the quest for efficiency in the actions and decisions related to organizational operations. On this basis, the aim of this study was to investigate what is the influence of collaborative performance management supply chain of organic coffee. Therefore, we carried out a research exploratory and descriptive in two stages. In the first step of this research, the exploratory nature of qualitative type was sought through interviews with professionals, determine elements to characterize the SCM organic coffee, as well as validate the indicators of collaboration and performance used in the study. The data collected through interviews with four managers, were treated for content analysis and contributed to the formation of characteristic elements of SCM and validate the constructs. In the second step was promoted research of descriptive type with quantitative questionnaires sent to managers involved in SCM organic coffee. Data were collected through questionnaires completed by 107 managers with experience in SCM organic coffee, treated statistically using factor analysis and structural equation development to analyze the relationships between the constructs SCM, collaboration and performance. The results showed valid relationship between the constructs [SCM and Cooperation] and [SCM & Performance]. However, it became clear that the collaboration had no influence on Operating Performance. Based on these results it can be concluded that although collaboration is valid for improving the performance of the SCM organic coffee, its importance was not evidenced by the executives. Finally, this research sought to contribute to broaden the knowledge about SCM's organic coffee and find grants in the corporate environment so that they can understand the potential impact of collaboration on operational performance of SCM organic coffee.